Association of Parent Training With Child Language Development - Kamelia, Kamelia; Nur Fatimah, Nur Fatimah (International Medical Journal Corp. Ltd, 2024)
Background: The association between parent training and child language development has garnered significant attention over the past two decades, as evidenced by a growing body of literature that explores various dimensions of this relationship. Literature Review: The reviewed literature collectively demonstrates the significant association between parent training and child language development across various contexts and populations. The studies illustrate that effective parent training programs can lead to improved knowledge and behaviors in parents, which subsequently enhances children's communicative abilities. Conclusion: In conclusion, the literature consistently underscores the critical role of parent training in enhancing child language development. The studies collectively advocate for targeted interventions that empower parents, foster collaboration between parents and professionals, and highlight the importance of tailored strategies to meet the diverse needs of families. Future research should continue to explore the long-term impacts of parent training and the effectiveness of various intervention models to further validate and refine practices in this essential area of child development.